Strategy Use Among Chinese as Second Language Learners in Mainland China From the Mediation Theory Perspective - Li, Chili; Chen, Lu; Ma, Chunyan; Zhang, Shuang; Huang, Haiquan (Frontiers in Psychology, 2021)
This paper reports a mixed-methods study that explored the strategy use of a cohort of Chinese as second language learners in mainland China from the perspective of mediation theory. Data sources include a questionnaire survey (N=189) and a semi-structured interview (N=12). The findings revealed that the participants orchestrated a repertoire of language learning strategies and frequently used social and meta-cognitive strategies. Analysis of the qualitative data suggested that the participants’ strategy use was shaped by the learners’ self agentic power (their beliefs and Ideal L2 self), and the socio-cultural environment. Specifically, their strategy use was mediated by a host of socio-cultural factors, including learner beliefs, social agents, cultural artefacts, and learning environment. Considered together, the findings illuminate the socially situated nature of the use of language learning strategy. That is, strategy use of the participants stems from the interplay of learner agency and socio-cultural factors. The findings also imply the necessity of strategy-based instruction and highlight the importance of a Chinese-speaking environment for Chinese learning.